Erzählungen – Erwartungen – Erfahrungen - Hartwig, Susanne (De Gruyter, 2024)
Surprising experiences with performers with intellectual disabilities can raise awareness of subliminal negative perceptions and open them to critique, e.g., in professional theater productions and films. This book examines productions and films against the backdrop of ideas of the everyday world using three analytical perspectives: narratives and expectations as meaningful contexts and experiences with disability.